Photochromic material as well as preparation method and application thereof

By developing a photochromic glass that can rapidly discolor under ultraviolet light irradiation in the 405nm band, the limitations of existing optical storage technology in storage capacity and speed are solved, high transparency and rapid photochromic reactions are achieved, and a wide range of information storage application prospects are provided.

CN119709171APending Publication Date: 2025-03-28KUNMING METALLURGY INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510018026.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing optical storage technology has bottlenecks in terms of storage capacity, and the cost and slow speed of writing information through femtosecond lasers or semiconductor lasers limits its practical application.

Method used

A photochromic material was developed to quickly change the glass from transparent to dark black by short-term exposure to a specific band of ultraviolet light (405nm) and exhibit obvious discoloration characteristics after 10 minutes under sunlight.

Benefits of technology

The high transparency and rapid photochromic reaction of photochromic glass are achieved, with potential multi-dimensional information storage application prospects, and reduce production costs and improve storage speed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119709171A_ABST
    Figure CN119709171A_ABST
Patent Text Reader

Abstract

The invention discloses a photochromic material and a preparation method and application thereof.The photochromic material is prepared from, by weight, 35-40 parts of germanium concentrate, 30-40 parts of B2O3, 8-10 parts of SiO2, 5-10 parts of Al2O3, 5-10 parts of SrCO3, 2-5 parts of AgCl, 0-0.2 part of Cu2O and 0-1 part of Dy2O3 through the steps of pretreatment, sintering and aftertreatment, and the raw materials comprise, by weight, 35-40 parts of germanium concentrate, 30-40 parts of B2O3, 8-10 parts of SiO2, 5-10 parts of Al2O3, 5-10 parts of SrCO3, 2-5 parts of AgCl, 0-0.2 part of Cu2O and 0-1 part of Dy2O3. The photochromic material disclosed by the invention not only has high transparency and good mechanical properties, but also shows obvious photochromic characteristics after being irradiated by a light source with the wave band of 405nm or sunlight. The response speed to a light source with the wave band of 405 nm is high, so that the material has great application potential in the fields of high-end automobile intelligent photochromic glass, optical storage and the like. In addition, the preparation method provided by the invention is simple and easy to implement, stable in process, high in production efficiency and beneficial to industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of materials, and in particular relates to a photochromic material and a preparation method and application thereof. Background Art

[0002] Optical technology has attracted much attention due to its significant environmental protection, energy saving and contactless operation advantages. Photochromic materials, as a kind of light memory material, will undergo visible color changes when irradiated by a specific light source and show obvious differences in the absorption spectrum. Therefore, they have broad application prospects in the fields of optical switching, optical storage and optical anti-counterfeiting.

[0003] With the advent of the information age and the explosive growth of data, traditional magnetic storage materials can no longer meet the demand. The development of new storage media is urgent, because the magnetism of magnetic materials will gradually weaken over time, which may cause information distortion or even loss, and the security of stored information faces severe challenges. Many examples show that the security of electronic archive storage materials has been threatened. Optical storage technology has become a promising solution for its energy saving, environmental protection and information storage persistence. However, due to the existence of grating diffraction limit, optical storage technology has encountered bottlenecks in storage capacity. Researchers continue to explore new methods to increase the capacity of optical information storage, and finally found that through information multiplexing technology, expanding the optical storage dimension (such as wavelength, intensity, polarization, life, etc.), and integrating multi-mode optical methods into a single technology based on appropriate recording media, the information storage capacity can be significantly improved. The future development direction of the storage industry may be that optical storage technology replaces traditional magnetic storage technology. Glass, as an excellent optical storage medium, has high transparency and makes it possible to write multi-dimensional optical information. However, the current high cost of storing multi-dimensional optical information in glass through expensive femtosecond lasers limits its practical application. In addition, the slow writing speed of writing information by semiconductor laser also limits the storage speed. Therefore, it is necessary to develop an optical storage medium that can write optical information quickly and at a low cost. Summary of the invention

[0004] In order to overcome the difficulties in the prior art, the photochromic material of the present invention is used to manufacture glass with a photochromic effect. By short-term irradiation with ultraviolet light (405nm) of a specific wavelength, the prepared photochromic glass can quickly change from a transparent state to a dark black state. In addition, the glass can also respond to sunlight and show obvious color change characteristics after 10 minutes of sunlight irradiation. The transparency and rapid photochromic reaction of this glass make it have potential application prospects in multi-dimensional information storage.

[0005] The first purpose of the present invention is to provide a photochromic material; the second purpose is to provide a method for preparing the photochromic material; and the third purpose is to provide an application of the photochromic material.

[0006] The first object of the present invention is achieved in that the photochromic material is prepared by pre-treatment, sintering and post-treatment steps of the following raw materials in parts by weight, wherein the raw materials include: 35-40 parts of germanium concentrate, 30-40 parts of B2O3, 8-10 parts of SiO2, 5-10 parts of Al2O3, 5-10 parts of SrCO3, 2-5 parts of AgCl, 0%-0.2 parts of Cu2O and 30-1 parts of Dy2O.

[0007] The second object of the present invention is achieved by comprising pre-treatment, sintering and post-treatment steps, specifically comprising: A. Pretreatment: Grind and mix the raw materials in the formula to obtain material a; B. Sintering: sintering material a in air atmosphere to obtain material b; C. Post-processing: 1) Keep material b at a temperature of 280-330°C for 8-12 minutes to obtain precursor material c; 2) Preserving the precursor material c at a temperature of 500-700°C for 3-8 hours to obtain the target material d; 3) Grinding and polishing the target material d to obtain the target photochromic material.

[0008] The specific operations are as follows: S1: weigh the raw materials according to the following proportions: germanium concentrate: 35%-40%, B2O3: 30%-40%, SiO2: 8%-10%, Al2O3: 5%-10%, SrCO3: 5%-10%, AgCl: 2%-5%, Cu2O: 0%-0.2%, Dy2O3: 0%-1%; then grind in an agate mortar; S2: The raw materials ground and mixed uniformly in S1 are moved to a high-temperature box furnace and sintered at 1350°C for 30 to 40 minutes in an air atmosphere; S3: The glass liquid is transferred to a brass mold preheated to 300°C and kept warm for 10 minutes to obtain a precursor glass; S4: Move the precursor glass in S3 to a small German furnace, keep it warm for 2 hours, and cool it to room temperature along with the furnace; S5: grinding and polishing the glass obtained in S4 on a polishing machine for 20 minutes to obtain a formed photochromic glass; S6: Using a spectrophotometer (U-4100) equipped with an integrating sphere, measure the transmittance spectrum of the glass before and after irradiation with 405 nm light. Preferably, the heat preservation in S4 is divided into two stages, and the heat preservation temperatures of the two stages are 550° C. and 600° C. respectively.

[0009] The present invention also provides an application of the photochromic effect glass prepared by the preparation method of the present invention in smart windows and optical information storage.

[0010] The third object of the present invention is achieved by using the photochromic material in the preparation of photochromic effect glass.

[0011] Silver halide doping inside glass can achieve a rapid photochromic effect. It has a fast light response speed, good transparency and excellent reversibility, and is considered to be an excellent optical storage medium. The excellent transparency makes it possible to write multi-dimensional information. In addition, due to its sunlight color change characteristics, it also provides new ideas for the development of smart windows.

[0012] Germanium is a dispersed element that is often found in zinc ores, especially those rich in zinc sulfide. In the zinc smelting process, germanium and zinc enter the smelting process at the same time. Part of the germanium will volatilize during the roasting process, but the other part will combine with impurities such as silicon and iron to form oxides or silicates that are not easily dissolved or volatilized, and finally enter and accumulate in the slag. Germanium-containing slag is mainly composed of silicates, oxides, germanium compounds, sulfides, iron and other impurities. This component contains various raw materials required for the composition of glass (such as network-forming tungsten oxide, network-modifying oxides, and network-external oxides), and can be used as an important raw material for the preparation of germanium-based glass. Therefore, the present invention proposes to use the germanium concentrate produced in the zinc smelting production process as a key raw material to design and develop germanium-based glass with photochromic properties; and by regulating the glass components, preparation process flow, heat treatment parameters, etc., the photochromic and self-bleaching properties of the germanium-based glass (including: light absorption rate, response rate, absorption range, anti-fatigue characteristics, etc.) are studied, the preparation process flow of the glass is optimized, and its potential applications in the field of high-end automotive intelligent color-changing glass and optical storage are developed.

[0013] The photochromic material of the present invention not only has high transparency and good mechanical properties, but also exhibits obvious photochromic properties after being irradiated by a light source in the 405nm band or sunlight. The response speed to the light source in the 405nm band is relatively fast, so it has great application potential in the fields of high-end automotive intelligent color-changing glass and optical storage. In addition, the preparation method proposed in the patent of the present invention is simple and easy, the process is stable, the production efficiency is high, and it is conducive to the realization of industrial production.

[0014] The beneficial effects of the present invention are: 1) The glass prepared by the present invention exhibits excellent transparency; 2) The present invention can rapidly exhibit reversible photochromic properties under 405nm wavelength light source irradiation; 3) After being irradiated with sunlight for 10 minutes, the glass of the present invention also undergoes obvious color change; 4) The glass of the present invention can quickly switch between transparent and opaque, has good fatigue resistance, and remains stable after multiple cycles; 5) The process of the present invention is simple and low in cost, and is expected to be applied in the fields of smart windows, optical storage, etc., and is expected to be industrialized. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 Schematic diagram of the glass with photochromic effect obtained in Example 1 of the present invention before and after color change; The picture shows that after being irradiated by a 405nm light source, the glass produces obvious photochromic characteristics; Among them, (a) is the picture of the glass in its initial state, and (b) is the picture after coloring; Figure 2 Schematic diagram of the glass with photochromic effect obtained in Example 2 of the present invention before and after color change; The picture shows that after being irradiated by a 405nm light source, the glass produces obvious photochromic characteristics; Among them, (a) is the picture of the glass in its initial state, and (b) is the picture after coloring; Figure 3 Schematic diagram of the glass with photochromic effect obtained in Example 3 of the present invention before and after color change; The figure shows: pictures of the glass with photochromic effect obtained in Example 3 of the present invention after being irradiated with sunlight for 10 minutes, (a) is a picture of the glass in its initial state, and (b) is a picture after being colored; Figure 4 It is a schematic diagram of the transmission spectrum before and after the color change induced by the 405nm band light source measured by the present invention; The figure shows that the transmittance of the glass is greatly reduced after photochromic treatment. DETAILED DESCRIPTION

[0016] The specific embodiments of the present invention are further described below in conjunction with the examples and drawings. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention.

[0017] The photochromic material of the present invention is prepared by pre-treatment, sintering and post-treatment of the following raw materials in parts by weight, wherein the raw materials include: 35-40 parts of germanium concentrate, 30-40 parts of B2O3, 8-10 parts of SiO2, 5-10 parts of Al2O3, 5-10 parts of SrCO3, 2-5 parts of AgCl, 0%-0.2 parts of Cu2O and 30-1 parts of Dy2O.

[0018] The method for preparing the photochromic material of the present invention comprises the steps of pre-treatment, sintering and post-treatment, and specifically comprises: A. Pretreatment: Grind and mix the raw materials in the formula to obtain material a; B. Sintering: sintering material a in air atmosphere to obtain material b; C. Post-processing: 1) Keep material b at a temperature of 280-330°C for 8-12 minutes to obtain precursor material c; 2) Preserving the precursor material c at a temperature of 500-700°C for 3-8 hours to obtain the target material d; 3) Grinding and polishing the target material d to obtain the target photochromic material.

[0019] The particle size of material a in step A is 200~300 mesh.

[0020] The sintering temperature in step B is 1200-1500°C.

[0021] The sintering time in step B is 30 to 40 minutes.

[0022] C Step 2) The heat preservation is divided into two stages.

[0023] The two-stage insulation is specifically as follows: the temperature of the first stage is 500-600°C, and the insulation time is 1-7h; the temperature of the second stage is 600-700°C, and the insulation time is 1-7h.

[0024] The temperature of the first insulation stage is 540-560° C., and the insulation time is 2-6 hours. The temperature of the second insulation stage is 640-660° C., and the insulation time is 1-2 hours.

[0025] The application of the photochromic material described in the present invention is the application of the photochromic material in the preparation of photochromic effect glass.

[0026] The present invention is further described below with specific implementation cases: Example 1 Preparation method based on glass with photochromic effect 1. Glass ratio design and raw material preparation - Calculate and weigh 10 g of raw materials according to the proportion of 35% germanium concentrate, 40% B2O3, 10% SiO2, 8% Al2O3, 5% SrCO3, 1.9% AgCl, 0.05% Cu2O, and 0.05% Dy2O3, and put them into an agate mortar.

[0027] 2. Raw material mixing and sintering -The mixed raw materials were moved to a high temperature box furnace and sintered at 1300°C for 30 minutes in an air atmosphere.

[0028] 3. Glass liquid processing -The sintered glass liquid was transferred to a brass mold preheated to 300°C and kept warm for 10 minutes to obtain the precursor glass.

[0029] 4. Heat treatment -The precursor glass was moved to a small German furnace and kept at 550°C for 4 hours, then cooled to room temperature in the furnace.

[0030] 5. Molding and polishing - The obtained glass was ground and polished on a polishing machine for 20 minutes to obtain a formed photochromic glass.

[0031] Effect display - The prepared transparent glass with photochromic properties is as follows Figure 1 As shown in (a), the glass heated at 550℃ for 4 hours appears slightly yellow.

[0032] -After irradiation with 405nm wavelength light source for 1 minute, the color of the glass changes from slightly yellow to black. Figure 1 (b) as shown.

[0033] Example 2 Preparation method based on glass with photochromic effect 1. Glass ratio design and raw material preparation - Calculate and weigh 10 g of raw materials according to the same ratio as in Example 1 and put them into an agate mortar.

[0034] 2. Raw material mixing and sintering -The mixed raw materials were moved to a high temperature box furnace and sintered at 1350°C for 30 minutes in an air atmosphere.

[0035] 3. Glass liquid processing -The sintered glass liquid was transferred to a brass mold preheated to 280°C and kept warm for 12 minutes to obtain a precursor glass.

[0036] 4. Heat treatment -The precursor glass was moved to a small German furnace and kept at 650°C for 2 hours, then cooled to room temperature in the furnace.

[0037] 5. Molding and polishing - The obtained glass was ground and polished on a polishing machine for 20 minutes to obtain a formed photochromic glass.

[0038] Effect display - The prepared transparent glass with photochromic effect is as follows Figure 2 As shown in (a), the glass heated at 650℃ for 2 hours appears slightly yellow.

[0039] -After irradiation with 405nm light source for 1 minute, the color of the glass changes from light yellow to dark black, and almost from transparent to opaque. Figure 2 (b) as shown.

[0040] Example 3 Preparation method based on glass with photochromic effect 1. Glass ratio design and raw material preparation - Calculate and weigh 10 g of raw materials according to the same ratio as in Example 1 and put them into an agate mortar.

[0041] 2. Raw material mixing and sintering -The mixed raw materials were moved to a high temperature box furnace and sintered at 1400°C for 30 minutes in an air atmosphere.

[0042] 3. Glass liquid processing -The sintered glass liquid was transferred to a brass mold preheated to 320°C and kept warm for 8 minutes to obtain a precursor glass.

[0043] 4. Heat treatment -The precursor glass was moved to a small German furnace and kept at 650°C for 2 hours, then cooled to room temperature in the furnace.

[0044] 5. Molding and polishing - The obtained glass was ground and polished on a polishing machine for 20 minutes to obtain a formed photochromic glass.

[0045] 6. Sunlight - The prepared glass was irradiated in sunlight for 10 minutes.

[0046] Effect display -The prepared transparent glass with photochromic effect, the glass kept at 650℃ for 2 hours showed a slight yellow color, such as Figure 3 (a) shown.

[0047] -After 10 minutes of exposure to sunlight, the glass color changes significantly, such as Figure 3 (b) as shown.

[0048] Example 4 Preparation method based on glass with photochromic effect 1. Glass ratio design and raw material preparation - Calculate and weigh 10 g of raw materials according to the proportion of 35% germanium concentrate, 40% B2O3, 10% SiO2, 5% Al2O3, 5% SrCO3, 1.9% AgCl, 0.05% Cu2O, and 0.05% Dy2O3, and put them into an agate mortar.

[0049] 2. Raw material mixing and sintering -The mixed raw materials were moved to a high temperature box furnace and sintered at 1450°C for 30 minutes in an air atmosphere.

[0050] 3. Glass liquid processing -The sintered glass liquid was transferred to a brass mold preheated to 300°C and kept warm for 10 minutes to obtain the precursor glass.

[0051] 4. Heat treatment -The precursor glass was moved to a small German furnace and kept at 650°C for 2 hours, then cooled to room temperature in the furnace.

[0052] 5. Molding and polishing - The obtained glass was ground and polished on a polishing machine for 20 minutes to obtain a formed photochromic glass.

[0053] 6. Spectrum test -The transmittance spectrum of the glass before and after irradiation with 405 nm light was measured using a spectrophotometer (U-4100) equipped with an integrating sphere.

[0054] Effect display -The prepared transparent glass with photochromic effect.

[0055] -There is a clear contrast between the transmission spectra before and after the color change. The light absorption in the visible band increases after photochromism, resulting in a sharp drop in the transmission spectrum after the color change.

[0056] Example 5 Comprehensive evaluation The transparent glass with photochromic effect obtained in Examples 1-4 of the present invention has a sintering temperature of 1200-1500°C, and is kept warm at 500-600°C and 600-700°C for 1-4 hours, respectively. The transmittance spectra before and after the color change at 500-700°C for 1-4 hours are measured, and the obtained slightly yellowish glass is glass with photochromic effect, and obvious photochromic phenomenon is produced according to the 405nm band light source and sunlight irradiation. Since the glass has excellent transparency and coloring performance, it has broad application prospects in the fields of smart windows, optical storage, etc.

Claims

1. A photochromic material, characterized in that: The photochromic material is prepared by pre-treatment, sintering and post-treatment of the following raw materials in parts by weight, wherein the raw materials include: 35-40 parts of germanium concentrate, 30-40 parts of B2O3, 8-10 parts of SiO2, 5-10 parts of Al2O3, 5-10 parts of SrCO3, 2-5 parts of AgCl, 0%-0.2 parts of Cu2O and 0-1 parts of Dy2O3.

2. A method for preparing the photochromic material according to claim 1, characterized in that: It includes pre-treatment, sintering and post-treatment steps, specifically including: A. Pretreatment: Grind and mix the raw materials in the formula to obtain material a; B. Sintering: sintering material a in air atmosphere to obtain material b; C. Post-processing: 1) Keep material b at a temperature of 280-330°C for 8-12 minutes to obtain precursor material c; 2) Preserving the precursor material c at a temperature of 500-700°C for 3-8 hours to obtain the target material d; 3) Grinding and polishing the target material d to obtain the target photochromic material.

3. The preparation method according to claim 2, characterized in that: The particle size of material a in step A is 200~300 mesh.

4. The preparation method according to claim 2, characterized in that: The sintering temperature in step B is 1200-1500°C.

5. The preparation method according to claim 2, characterized in that: The sintering time in step B is 30 to 40 minutes.

6. The preparation method according to claim 2, characterized in that: C Step 2) The heat preservation is divided into two stages.

7. The preparation method according to claim 6, characterized in that: The two-stage insulation is specifically as follows: the temperature of the first stage is 500-600°C, and the insulation time is 1-7h; the temperature of the second stage is 600-700°C, and the insulation time is 1-7h.

8. The preparation method according to claim 7, characterized in that: The temperature of the first insulation stage is 540-560° C., and the insulation time is 2-6 hours. The temperature of the second insulation stage is 640-660° C., and the insulation time is 1-2 hours.

9. An application of the photochromic material according to claim 1, characterized in that: The photochromic material is used in preparing photochromic effect glass.